Soil Management in the Breede River Valley Wine Grape Region, South Africa. 3. Grapevine Performance - Fourie, J.C. (South African Journal of Enology and Viticulture, 2011)
Eight cover crop treatments were applied for 12 consecutive years on a medium textured soil in a vineyard near Robertson (33o50’S, 19o54’E). A treatment with full surface straw mulch combined with full surface post-emergence chemical control applied from just before grapevine bud break to harvest (BB) and another with no cover crop combined with BB was also applied. The control consisted of mechanical control in the work row and post-emergence chemical control in the vine row applied from bud break to harvest. In the BB treatments, grapevine shoot growth was significantly higher than in the treatment where a perennial cover crop was established in the work row during both the second (1993/94) and third (1994/95) season after the grapevines were established. The grape yield in all the BB treatments, except the one in which a mixture of Secale cereale L. v. Henog and Vicia faba L. v. Fiord was sown, was significantly higher than that of the control and the treatment in which a perennial cover crop was sown in the work row during the 1995/96 season. During the 2001/02 season, the grape yield of the BB treatment with a full surface straw mulch was significantly higher than that of all the other treatments. The different soil management practices had a significant effect on the N status of the juice, but did not affect wine quality.